A high-performance sandwiched-porous polybenzimidazole membrane with enhanced alkaline retention for anion exchange membrane fuel cells1. Issue 9 (26th September 2015) - Zeng, L.; Zhao, T. S.; An, L.; Zhao, G.; Yan, X. H.
<x xml:space="preserve">Abstract</x> Polybenzimidazole (PBI)-based membrane electrode assemblies are fabricated with a sandwiched-porous PBI as the membrane and a new catalyst structure using PBI-decorated reduced graphene oxide as the supporting material for anion exchange membrane fuel cells.